Starbucks Marketing Strategy - Agarwal, Varsha (International Journal of Scientific Development and Research, 2022)
As coffee shops change into spaces that offer clients a range of experiences, coffee acts as a medium. Coffee shops are simple settings where people may enjoy and share their cultures while having coffee, but they also reflect the distinct personalities and values of their customers. Given this evolution, it is important to take into account the coffee shop in terms of spatial design marketing as a setting with virtually endless possibilities to effectively communicate the needs of modern customers through spatial identity and story. Target market is one of the most important marketing decisions for most companies. Its aim is to identify and delineate market segments which would become targets for the company’s marketing plan. Starbucks segmentation and targeting consist of a marketing decision in identifying the appropriate group of people among the general public of future customers for the business and targeting this segment via positioning products and services that resonate well with their need and wants.The aim of this research paper is to identify the market strategy of starbucks and how it can be improved.
ISME
Keywords: segmentation; market strategy; coffee; customers; marketing